Potential Risk Factors Influencing the Indian Pharmaceutical Industry - An Exploratory Study - John, V. Y. (Indian Journal of Finance, 2009)
The Indian Economy has been growing at a phenomenal growth rate of more than 8.5% during the period 2003-08. "Pharmaceutical industry's growth moved in tandem with the economy's growth rate which has been growing at a Compounded Annual Growth Rate of 7.7% during the last five years and during the year 2005, was $5.1 billion in size in comparison with the global pharmaceutical market which stood at $ 550 billion in size" Companies like Ranbaxy Laboratories, Dr.Reddy's Laboratories, Wockhardt Ltd. are eying for lucrative acquisitions. Leading pharmaceutical companies are pursuing inorganic growth routes and expanding their operations across the world pursuing their goal of aggressive growth and diversification. It is observed that there is an exponential growth in the size of the operations, number of countries to which exports are being made and different segments of products catering to diseases like AIDS, cardiovascular, gastro enteric, carcinogenic and lifestyle diseases. The industry is facing many severe challenges, opportunities and constraints from the government, market forces in the national and international markets, customers, regulatory bodies and its operations within.Many issues like cost overruns, quality assurance systems, low margins, researching, developing and launching new products, phasing out unviable products, diversifying into new lines of business and the like keep arising in the course of operations of most of the leading pharmaceutical firms which need to be resolved by the management of the firm. Many of the leading pharmaceutical companies in India are enlarging their exports to regulated markets.